Insisting upon Meaningful Results from Adsorption Experiments. Issue 2 (3rd April 2022) - Hubbe, Martin A.
ABSTRACT: A rigorous approach to adsorption studies is advocated in this review article as a means to improving the experience of researchers and improving the practical value of published work in the field. Three broad areas of concern are considered in this article: mistakes related to the experimental conditions selected, mistakes related to modeling of results, and mistakes related to the mind-set of the investigators. Adsorption experiments can be perceived as an excellent training ground within which to hone the skills of researchers, including experimental methods, the use of statistics, and the ability to find suitable equations by referring to published literature. There is potential to increase the value to society of the results of such work by insisting upon the acquisition of truly meaningful results, in addition to accurately following research strategies laid out in published work. Examples related to adsorption onto cellulosic materials are emphasized in this article.